Gastroenteropancreatic Neuroendocrine Tumors in Multiple Endocrine Neoplasia Type 1 - Maria Luisa Brandi (Cancers, 2012)
We reviewed the literature about entero-pancreatic neuroendocrine tumors in Multiple Endocrine Neoplasia type 1 syndrome (MEN1) to clarify their demographic features, localization imaging, practice, and appropriate therapeutical strategies, analyzing the current approach to entero-pancreatic neuroendocrine tumors in MEN1. Despite the fact that hyperparathyroidism is usually the first manifestation of MEN1, the penetrance of these tumors is similar. They are characterized by multiplicity of lesions, variable expression of the tumors, and propensity for malignant degeneration. Both the histological type and the size of MEN1 neuroendocrine tumors correlate with malignancy. Monitoring of pancreatic peptides and use of imaging exams allow early diagnosis and prompt surgical treatment, resulting in prevention of metastatic disease and improvement of long-term survival. Surgery is often the treatment of choice for MEN1-neuroendocrine tumors. The rationale for surgical approach is to curtail malignant progression of the disease, and to cure the associated biochemical syndrome, should it be present.